2018
DOI: 10.1038/s41586-018-0251-7
|View full text |Cite
|
Sign up to set email alerts
|

Acquired resistance to IDH inhibition through trans or cis dimer-interface mutations

Abstract: Somatic mutations in the isocitrate dehydrogenase 2 gene (IDH2) contribute to the pathogenesis of acute myeloid leukaemia (AML) through the production of the oncometabolite 2-hydroxyglutarate (2HG). Enasidenib (AG-221) is an allosteric inhibitor that binds to the IDH2 dimer interface and blocks the production of 2HG by IDH2 mutants. In a phase I/II clinical trial, enasidenib inhibited the production of 2HG and induced clinical responses in relapsed or refractory IDH2-mutant AML. Here we describe two patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
202
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(213 citation statements)
references
References 26 publications
9
202
2
Order By: Relevance
“…Interestingly, the D273 homolog in IDH2, D312, is located on the same side of the helix and only 5.3 Å from Q316 IDH2, a residue involved in acquired resistance to mutant IDH2 inhibitor binding. Q316E IDH1 has been identified in patients treated with the selective mutant IDH2 inhibitor Enasidenib (103), and results in resistance to this drug (104). Thus, our reported decrease in affinity for mutant IDH1 inhibitors is not surprising when considering the proximity of D273 to the allosteric pocket (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Interestingly, the D273 homolog in IDH2, D312, is located on the same side of the helix and only 5.3 Å from Q316 IDH2, a residue involved in acquired resistance to mutant IDH2 inhibitor binding. Q316E IDH1 has been identified in patients treated with the selective mutant IDH2 inhibitor Enasidenib (103), and results in resistance to this drug (104). Thus, our reported decrease in affinity for mutant IDH1 inhibitors is not surprising when considering the proximity of D273 to the allosteric pocket (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…We found that the thermal-stabilizing effects of TQ05310 and AG-221 were lost in U-87 MG/IDH2-R140Q-Q316A cells, suggesting the critical role of the Q316 residue in binding these two inhibitors with IDH2-R140Q, and that the Q316 mutation may cause resistance to these inhibitors in patients with IDH2-R140Q. Notably, a study based on clinical observation reported that an AML patient with IDH2-R140Q showed an initial clinical response to AG-221, but developed drug resistance and disease progression after the emergence of the Q316E mutation in IDH2, 31 which confirmed the critical role of the Q316 residue in drug sensitivity. Collectively, these results indicate that monitoring Q316 mutations is important to predict the effectiveness of AG-221 and TQ05310 in patients harboring the IDH2-R140Q mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Response to IDH inhibitors appears greater among patients with fewer concomitant mutations, which may explain the trend for higher response rates when patients are treated at earlier stages of disease. Interestingly, late relapses have been reported in association with rising 2‐HG and noncatalytic second site mutations located at the homodimer interface …”
Section: The Challenge Of Relapsed and Refractory (R/r) Amlmentioning
confidence: 99%
“…Interestingly, late relapses have been reported in association with rising 2-HG and noncatalytic second site mutations located at the homodimer interface. 110 In the frontline AML setting, enasidenib produces CR/CRi of 21%-43% 111,112 and ivosidenib produces CR/CRh of 41%. 113 The median time to first response and CR to IDH inhibitors are approximately 1.9 months and 2.8 to 3.7 months, respectively, which can be challenging for patients with active disease needing to sustain therapy for several months without certainty of an eventual response.…”
Section: Idh1/2 Inhibitorsmentioning
confidence: 99%